Perceptions of inequality in Costa Rica: institutional factores, political system and mass media - Robles-Rivera, Francisco (2025)
Costa Rica is one of the most unequal countries in the world. In recent years, despite a rising inequality, this Central American country continues to uphold imaginaries that support a sense of exceptionality rooted in national myths associated with equality. This article examines Costa Rican perceptions of inequality through a cross-sectional, descriptive, and exploratory quantitative study. For this purpose, the study utilizes the Survey on Freedom of Expression and Trust in the Media conducted by the Center for Research and Political Studies (CIEP) for the Program on Freedom and the Right to Information (PROLEDI 2023). The analysis reveals that factors such as older age and greater trust in public universities are associated with higher perceptions of increasing inequality. Conversely, the data suggest that higher levels of trust in legislators and more frequent consumption of radio and print newspapers are related to lower perceptions of a rising  inequality. The article proposes a discussion on institutional, media, and political system factors to explore how the population interprets the increase in economic inequality in Costa Rica.